The role of readiness to change and other patient factors in the prediction of dropout from treatment-for problem drinking of alcohol. - Saban, Amina (Department of Psychology, 2023)
The main purpose of the study was examining the predictive role of patients' readiness to change drinking behaviour, in drought from treatment for problem drinking. The predictive role of patient demographic factors, socioeconomic factors, personal history and drinking factors in drought from treatment for problem drinking was also examined. A subsidiary interest of the study was to examine the differences between patients who completed their treatment and patients who did not complete their treatment for problem drinking. The study was conducted at Avaloo Treatment Centre, an alcohol treatment centre in Cape Town, South Africa. The subjects consisted of all inpatients and daypatieots who were admitted to the Avalon Treatment Centre Rehabilitation Programme over a period of five consecutive months (n == 62). Information for the study was elicited from the subjects by means of an interview schedule designed for the study, and the Readiness to Change Questionnaire (Treatment Version) which was developed by Heather, Luce, James, Peck and Dunbar (1996). The interview schedule consisted of four main sections that requested information about patient demographic characteristics, socioeconomic characteristics, personal and drinking history factors, and information regarding discharge from treatment at Avalon Treannent Centre. The researcher conducted the interviews and administered the Readiness to Change Questionnaire (Treatment Version) to all the subjects. Information relating to patient discharge was obtained from the patients' folders, the patients themselves, the patients' families, and from the Avalon Treatment Centre therapeutic staff. The results of the study are described. The data was analysed statistically by means of bivariate analyses (such as chi square tests) and multivariate statistical analyses (namely, discriminant function analysis). The findings indicated that statistically, significantly more daypatieots ~ped out of the Rehabilitation Programme than did inpatients. The discriminant function analysis suggested that six patient factors contributed significantly to the discrimination between dropouts and completers of treatment for problem drinking of alcohol. The patient factors were wine, the alcoholic beverage consumed most frequently; drinking alcoholic beverages daily; living alone at the time of the admission for treatment via the Rehabilitation Programme; being separated from spouse at the time of admission; the Preparation-Action stage of change; previous treatment for problem drinking. These results indicated that dropout from treatment for problem drinking could be reliably predicted from patient characteristics. The results also suggested that there are significant differences between dropouts and completers of treatment for problem drinking. The results are discussed 111 the light of related research: findings, and possible explanations for the: findings are offered. Recommendations for the implementation of the findings and their implications for future research are suggested.